Lymphoma or Brucellosis: A Case Series Study - Parsa Rostami; Shiva Shabani; Azin Ahmari (Case Reports in Clinical Practice)
Human Brucellosis is a zoonotic disease with various clinical manifestations, ranging from asymptomatic infection to multisystem involvement. Cases with hematological abnormalities and lymphadenopathy, which were referred to the hematology department of the hospital, were described from September 2021 to August 2022. These Iranian patients included a 38-year-old man and two 64- and 24-year-old women. Due to the region’s endemicity and strong clinical suspicion of brucellosis, therapeutic management and invasive procedures such as splenectomy were avoided in one case. Based on the available literature, it is evident that the infrequent symptoms that accompany the typical symptoms of brucellosis may give rise to uncertainty and hinder prompt diagnosis. The reason is that patients presenting with indications of pancytopenia, coupled with splenomegaly or lymphadenopathy, are typically referred to hematologists. Hence, the purpose of these case reports is to highlight the symptoms of brucellosis that mimic a primary hematologic disorder, facilitating faster and more accurate diagnosis.